Message-oriented communication for IPv6-enabled pervasive devices - Szydło, Tomasz; Suder, Paweł; Bibro, Jakub (Wydawnictwa AGH, 2013)
An increasing number of electronic devices are being equipped with radio interfaces intended for communication with and control by other devices and applications. Wireless communication in this class of devices may be exposed to a number of situations that can occur, including limited energy resources, equipment failures, node mobility, and loss of communication between nodes. Ultimately, commonly-used standards and protocols for sharing services are not practical and do not take into account the occurrence of such problems. This paper presents a concept of communication that relies on the exchange of messages between wireless-pervasive devices commonly found in our environment.
Computer Science
Bibliogr. s. 676-677.
Keywords: sensor setworks; IPv6; message-oriented middleware